A phosphofructokinase B-type carbohydrate kinase family protein, PFKB1, is essential for chloroplast development at early seedling stage in rice - Zhu, Xiaobo (Plant science : an international journal of experimental plant biology, 2020)
Copyright © 2019 Elsevier B.V. All rights reserved.